Expressway pavement structure capable of utilizing waste residues
By using prestressed concrete layer and cement waste slag to stabilize the base layer of wind-and-sand in the highway pavement structure, combined with the stone-embedded interface treatment and modified asphalt bonding layer, the disease problems of asphalt pavement under heavy traffic and coal-fired power plants are solved. The problem of waste treatment has achieved resource utilization and improved technical performance.
Patent Information
- Application Number
- CN202411685459.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2020-05-07
- Publication Date
- 2025-01-17
AI Technical Summary
In the prior art, asphalt pavement is prone to diseases under heavy traffic conditions, and the solid waste treatment method of coal-fired power plants has problems such as large area, high environmental pressure and high treatment costs. There is a shortage of road construction materials in wind-abundant sand areas. Traditional pavement structures are prone to dangers such as wind erosion and sand burial, and the maintenance and management cost is high.
The bottom-up laid waste slag is used to utilize the highway pavement structure, including prestressed concrete layer, cement waste slag stabilizes the base layer of the sand and the base layer, and improves the shear resistance of the pavement through the stone embedded interface treatment and SBR modified emulsified asphalt bonding layer. Strength and compressive strength, and use AC13 or AC16 asphalt surfaces in asphalt surfaces to improve anti-slip properties.
It improves the bending tensile strength and shear strength of the pavement structure, extends the service life of the asphalt pavement structure, realizes the resource utilization of waste slag and wind-abundant sand in power plant, reduces engineering cost, reduces environmental pollution, and improves wind-abundant sand in wind-abundant sand in wind-abundant sand. road construction technology level.
Smart Images

Figure CN119321075A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of pavement structures, and in particular to a highway pavement structure utilizing waste residues. Background Art
[0002] In recent years, asphalt pavement often suffers from diseases under the action of heavy traffic, thus affecting the service life of the pavement. On the other hand, with the continuous deepening of industrialization, industrial solid waste is increasing year by year. As the main body of the energy industry, coal-fired power plants generate solid waste every year, which not only puts great pressure on the surrounding environment, but also causes waste of resources.
[0003] Solid waste from coal-fired power plants (i.e., power plant slag) is mainly generated during the coal-fired power generation process. After high-temperature combustion, coal powder forms a volcanic ash-like mixed material, mainly including fly ash, slag, debris, etc. In addition, with the maturity of desulfurization technology conditions, desulfurized gypsum has become a major solid waste from modern coal-fired power plants. Pollution of solid waste from coal-fired power plants The chemical harmful components in the solid waste from coal-fired power plants that are stored in the open air or placed in disposal sites can be directly or indirectly transmitted to the human body through environmental media - the atmosphere, soil, surface or groundwater, etc., threatening health. Power plant slag refers to the sintered coarse slag discharged from the bottom of the furnace after the coal in the power plant is burned in the boiler. It occupies a large amount of land for accumulation, aggravates the contradiction in land use, greatly damages land resources, and also causes a variety of environmental problems.
[0004] At present, the solid waste from coal-fired power plants is mainly disposed of by landfill and stacking, which occupies a large area, has great environmental pressure, high disposal cost and serious waste. Research on resource utilization of solid waste from coal-fired power plants can achieve the dual effects of saving resources and protecting the environment.
[0005] In addition, aeolian sands are widely distributed in Northwest my country, accounting for about 17.9% of the country's total land area. Aeolian sand regions are rich in natural resources. For example, the proven oil and gas resources in the Taklimakan Desert alone amount to 16 billion tons. The Shenfu coalfield, located on the southern edge of the Maowusu Desert, is the largest proven coalfield in my country, accounting for 15% of the country's proven reserves. The transportation facilities in aeolian sand regions are weak. Building roads in aeolian sand regions can further improve the road network structure in the western region and promote resource development and social and economic development in the western region.
[0006] The problems faced in building roads in wind-blown sand areas are: lack of road construction materials, the construction of traditional road structures mostly uses lime soil, sand and gravel and other materials, which need to be transported over long distances and are expensive. There is still a lack of systematic research and summary on the engineering application of wind-blown sand in China. After completion, the road may also face hazards such as wind erosion and sand burial, and the maintenance and management costs are high. Summary of the invention
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a highway pavement structure utilizing waste slag, which has a simple pavement structure, can achieve effective utilization of power plant waste slag and aeolian sand, has a low production cost, and the resulting pavement structure meets the requirements of the "Technical Specifications for Highway Pavement Base Construction" (JTG / TF20-2015).
[0008] In order to achieve the above object, the present invention adopts the following technical solutions to achieve it.
[0009] A highway pavement structure utilizing waste residues, comprising a subbase layer, a base layer, a lower layer and an upper layer laid from bottom to top; wherein:
[0010] The upper layer is an AC13 or AC16 asphalt surface layer, which is used as a functional layer and a wear layer of the pavement structure, and plays a role in preventing the pavement from skidding and improving driving comfort. If the functional layer does not meet the anti-skid requirements and usage conditions, it is milled and then a new wear layer is paved;
[0011] The lower layer is a prestressed concrete layer, which is made of cement concrete with a flexural tensile strength of 5MPa. The prestressed tendons are arranged at an angle of 30-45 degrees and a spacing of 0.5m-1m.
[0012] The interface treatment process of the prestressed concrete layer is: embed the crushed stone into the concrete, that is, the stone embedding interface, and then spread SBR modified emulsified asphalt as a bonding layer. The spreading amount of the bonding layer is 0.9L / m 2 , the bonding layer is used to enhance the shear strength between the prestressed concrete layer and the asphalt surface layer;
[0013] The base layer is a cement waste slag stabilized gravel and aeolian sand base layer, which is made of gravel, power plant waste slag, cement and aeolian sand;
[0014] The base layer is a cement waste slag stabilized aeolian sand base layer, which is made of cement, power plant waste slag and aeolian sand.
[0015] Preferably, the thickness of the upper layer is 3-5 cm.
[0016] Preferably, the thickness of the lower layer is 20-24 cm.
[0017] Preferably, the thickness of the base layer is 18-20 cm.
[0018] Preferably, the thickness of the base layer is 18-20 cm.
[0019] Preferably, the cement waste slag stabilized aeolian sand subbase comprises 5%-7% cement, 20%-50% power plant waste slag, and the remainder is aeolian sand.
[0020] Preferably, the cement waste slag stabilized gravel aeolian sand base layer comprises 30%-40% gravel, 20-30% power plant waste slag, 6%-8% cement, and the remainder is aeolian sand.
[0021] Preferably, the particle size of the crushed stone is 10-30 mm.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The waste residue-utilized highway pavement structure of the present invention uses a prestressed concrete layer as the lower layer. Taking advantage of the high strength of prestressed concrete, longitudinal and transverse compressive stresses are applied to the pavement by applying oblique prestress, thereby improving the bending and tensile strength of the concrete plate. The original bending and tensile strength of the concrete is designed to be 5MPa. After the prestress is applied, the strength can be increased by 20%-40%. The interface of the prestressed concrete layer adopts the stone embedding process to form a rivet connection with the asphalt surface layer, thereby improving the shear strength between the layers. Compared with the smooth concrete (shear strength 0.674), the shear strength can be increased by 70%.
[0024] (2) The present invention uses power plant waste slag to replace part of the aeolian sand in the cement-stabilized aeolian sand base layer, which is beneficial to improving its compressive strength. The obtained cement waste slag-stabilized aeolian sand base layer has a 7-day unconfined compressive strength of 2.0-2.8 MPa and a 28-day unconfined compressive strength of 4.3-5.9 MPa, which meets the requirements of heavy traffic roads.
[0025] (3) The strength of the cement waste slag stabilized gravel aeolian sand base can still meet the requirements of the Technical Specifications for Highway Pavement Base Construction (JTG / T F20-2015).
[0026] (4) The highway pavement structure utilizing waste residue of the present invention realizes the application of power plant waste residue and aeolian sand in the pavement structure, and while realizing the resource utilization of industrial power plant waste residue and aeolian sand, the service life of the asphalt pavement structure is improved. At the same time, aeolian sand can be obtained locally, and the road is built using abundant and cheap aeolian sand resources, which can not only ensure the construction quality and technical performance of the highway project, but also greatly reduce the project cost, achieve energy conservation and emission reduction, protect the ecological environment, and improve the road construction technology level in aeolian sand areas. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0028] Figure 1A schematic diagram of a highway pavement structure utilizing waste residues according to the present invention;
[0029] Figure 2 This is a comparison chart of the screening results of power plant waste slag before and after compaction;
[0030] Figure 3 This is the scattering diagram of pure coal slag after 7 days of immersion in water;
[0031] In the above figure: 1 bottom layer; 2 base layer; 3 lower layer; 4 upper layer. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0033] In the description of the present invention, it is necessary to understand that the terms "upper", "lower", "front", "back", "left", "right", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0034] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "set" should be understood in a broad sense, for example, they can be fixedly connected or set, or detachably connected or set, or integrally connected or set. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0035] refer to Figure 1 A highway pavement structure utilizing waste residues comprises a subbase layer 1, a base layer 2, a lower layer 3 and an upper layer 4 laid from bottom to top. The entire highway pavement structure utilizing waste residues is constructed by paving with an asphalt paver.
[0036] Specifically:
[0037] (1) The upper layer 4 is a 3-5 cm AC13 or AC16 asphalt surface layer, which is the functional layer and wear layer of the pavement structure, and plays a role in preventing the pavement from skidding and improving driving comfort. If the functional layer does not meet the anti-skid requirements and usage conditions, it will be milled and then a new wear layer will be laid.
[0038] (2) The lower layer 3 is a prestressed concrete layer, which uses cement concrete with a flexural tensile strength of 5 MPa. The prestressed tendons are arranged at an angle of 30 degrees to 45 degrees and at a spacing of 0.5 m to 1 m.
[0039] The prestressed concrete layer adopts the interface treatment process: the crushed stones are embedded in the concrete, that is, the stone-embedded interface, and then the SBR modified emulsified asphalt is spread as the bonding layer. The spreading amount of the bonding layer is 0.9L / m 2 The setting of the bonding layer can enhance the shear strength between the prestressed concrete layer and the asphalt surface layer.
[0040] (5) The base layer 2 is a cement waste slag stabilized gravel aeolian sand base layer 2, which uses 30%-40% 10-30 mm gravel, 20%-30% power plant waste slag, 6%-8% cement, and the balance is aeolian sand.
[0041] (6) The base layer 1 is a cement waste slag stabilized aeolian sand base layer 1, which includes 5%-7% cement, 20%-50% power plant waste slag, and the remainder is aeolian sand.
[0042] Among them, the screening results of the above-mentioned aeolian sand are shown in Table 1.
[0043] Table 1 Aeolian sand screening results (square hole sieve)
[0044]
[0045] The chemical composition, sieve pass rate and adhesion of the power plant waste slag before and after compaction were analyzed as follows:
[0046] 1. Chemical composition analysis of power plant waste residue
[0047] The waste slag from coal-fired power plants was sampled and analyzed for chemical composition. The results are shown in Table 2.
[0048] Table 2 Chemical composition analysis results of waste residue from coal-fired power plants
[0049] Test items Units of measurement Test results CaO % 4.44 <![CDATA[Al2O3]]> % 13.26 <![CDATA[Fe2O3]]> % 9.37 <![CDATA[SiO2]]> % 66.12 <![CDATA[SO3]]> % 0.68 Loss on ignition % 0.53
[0050] As shown in Table 2, the main oxide components of power plant waste residue are silicon oxide (SiO2), aluminum oxide (Al2O3), iron oxide (Fe2O3), and calcium oxide (CaO); among them, silicon oxide, aluminum oxide, iron oxide, and calcium oxide account for 93.19% of the total, indicating that power plant waste residue has certain activity. It can be seen that the application of power plant waste residue in highway engineering is feasible.
[0051] 2. Analysis of sieve pass rate of power plant waste slag before and after compaction
[0052] The sieve pass rate of power plant waste slag before and after compaction was analyzed. The results are shown in Table 3 and Figure 2 shown.
[0053] Table 3 Screening results of power plant waste slag before and after compaction
[0054]
[0055] From Table 3 and Figure 2 It can be seen that due to the high crushing value of power plant waste slag, the gradation of power plant waste slag before and after compaction changes significantly. Under the action of the compaction hammer, the pass rate of 16mm and 13.2mm sieve holes changes slightly, less than 10%; the pass rate of 9.5mm sieve holes changes by about 13%; the pass rate of 4.75mm and 2.36mm sieve holes changes the most, about 20%; the pass rate of fine aggregates from 0.15mm to 1.18mm sieve holes changes by more than 10%. This shows that the power plant waste slag is crushed under the action of compaction, and the overall pass rate increases.
[0056] 3. Analysis of Adhesiveness of Power Plant Waste Slag
[0057] The unconfined specimens were made of pure power plant waste slag and their adhesion was tested without adding cement. The results are as follows: Figure 3 shown.
[0058] Depend on Figure 3 It can be seen that the unconfined specimens of pure power plant waste slag will disperse when exposed to water and are very easy to break. This shows that pure power plant waste slag has no adhesiveness.
[0059] Example 1
[0060] Cement waste slag stabilized aeolian sand subbase 1: includes 7% cement, 20% power plant waste slag and 73% aeolian sand.
[0061] Example 2
[0062] Cement waste slag stabilized aeolian sand subbase 1: includes 7% cement, 30% power plant waste slag and 63% aeolian sand.
[0063] Example 3
[0064] Cement waste slag stabilized aeolian sand subbase 1: includes 7% cement, 40% power plant waste slag and 53% aeolian sand.
[0065] Example 4
[0066] Cement waste slag stabilized aeolian sand subbase 1: includes 7% cement, 50% power plant waste slag and 43% aeolian sand.
[0067] Comparative Example 1
[0068] Cement stabilized aeolian sand subbase 1: includes 7% cement and 93% aeolian sand.
[0069] Test 1
[0070] Test method: The 7-day compressive strength and coefficient of variation of the cement waste slag stabilized aeolian sand subbase 1 with different amounts of power plant waste slag obtained in Examples 1-4 and the cement stabilized aeolian sand subbase 1 obtained in Comparative Example 1 were tested respectively. The test method refers to the "Test Code for Stabilized Materials with Inorganic Binders for Highway Engineering" JTG E51 (T0805).
[0071] Test results: The test results are shown in Table 4.
[0072] Table 4 Test results of cement stabilized aeolian sand subbase 1 and cement waste slag stabilized aeolian sand subbase 1
[0073]
[0074] As shown in Table 4, the 7-day compressive strength of Examples 1-4 increases successively, and the 28-day compressive strength increases successively, indicating that the compressive strength of the cement waste slag stabilized aeolian sand subbase 1 gradually increases with the increase of the amount of power plant waste slag; when the amount of power plant waste slag is 50%, the 7-day compressive strength of the cement waste slag stabilized aeolian sand subbase 1 reaches a maximum value of 2.8MPa, and the 28-day compressive strength reaches a maximum value of 5.9MPa. The 7-day compressive strength of the cement waste slag stabilized aeolian sand subbase 1 in Examples 1-4 with 20%, 30%, 40%, and 50% of power plant waste slag added is greater than the 7-day compressive strength (1.5MPa) of the cement stabilized aeolian sand subbase 1 of Comparative Example 1, indicating that using power plant waste slag to replace part of the aeolian sand in the cement stabilized aeolian sand subbase 1 is beneficial to improve its compressive strength.
[0075] Test 2
[0076] The 7d compressive strength and coefficient of variation of cement stabilized aeolian sand and cement waste slag stabilized gravel aeolian sand base 2 were tested, and the test results are shown in Table 5 and Table 6 respectively.
[0077] Table 5 7d compressive strength test results of cement stabilized aeolian sand
[0078] Cement: Aeolian sand Average value / MPa Coefficient of variation / % 5:95 0.7 5.1 6:94 1.2 5.7 7:93 1.5 3.4 8:92 2.2 2.4 9:91 2.7 1.9
[0079] Table 6 7d compressive strength of cement waste slag stabilized gravel aeolian sand base 2
[0080]
[0081] It can be seen from Tables 5 and 6 that the 7d unconfined compressive strength of the cement waste slag stabilized gravel aeolian sand base 2 is significantly higher than that of the cement stabilized aeolian sand. And the 7d unconfined compressive strength of the cement waste slag stabilized gravel aeolian sand base 2 of the present application can reach 3.4-4.2MPa when the cement dosage is 6%, and the 7d unconfined compressive strength can reach 4.5-5.6MPa when the cement dosage is 7-8%.
[0082] The existing "Technical Specifications for Construction of Highway Pavement Base 2" (JTG / T F20-2015) has the following standard requirements for the 7d unconfined compressive strength of highway structural layers, as shown in Table 7.
[0083] Table 7 Standard requirements for highway structural layers
[0084]
[0085] It can be seen from Table 4 and Table 7 that the 17d unconfined compressive strength of the cement waste slag stabilized aeolian sand subbase is 2.0-2.8MPa, which meets the requirements of the subbase structure 1 of heavy traffic roads.
[0086] It can be seen from Tables 6 and 7 that the 7d unconfined compressive strength of the cement waste slag stabilized gravel aeolian sand base 2 of the present application can reach 3.4-4.2MPa when the cement dosage is 6%, which meets the structural requirements of the base 2 of medium and light traffic roads; when the cement dosage is 7-8%, the 7d unconfined compressive strength can reach 4.5-5.6MPa, which meets the structural requirements of the base 2 of extremely heavy and extra-heavy traffic roads.
[0087] Although the present invention has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A highway pavement structure utilizing waste residue, characterized in that: It includes the subbase, base layer, lower layer and upper layer laid from bottom to top; among which, The upper layer is an AC13 or AC16 asphalt surface layer, which is used as a functional layer and a wear layer of the pavement structure, and plays a role in preventing the pavement from skidding and improving driving comfort. If the functional layer does not meet the anti-skid requirements and usage conditions, it is milled and then a new wear layer is paved; The lower layer is a prestressed concrete layer, which is made of cement concrete with a flexural tensile strength of 5MPa. The prestressed tendons are arranged at an angle of 30-45 degrees and a spacing of 0.5m-1m. The interface treatment process of the prestressed concrete layer is: embed the crushed stone into the concrete, that is, the stone embedding interface, and then spread SBR modified emulsified asphalt as a bonding layer. The spreading amount of the bonding layer is 0.9L / m 2 , the bonding layer is used to enhance the shear strength between the prestressed concrete layer and the asphalt surface layer; The base layer is a cement waste slag stabilized gravel and aeolian sand base layer, which is made of gravel, power plant waste slag, cement and aeolian sand; The base layer is a cement waste slag stabilized aeolian sand base layer, which is made of cement, power plant waste slag and aeolian sand.
2. The highway pavement structure utilizing waste residue according to claim 1 is characterized in that: The thickness of the upper layer is 3-5 cm.
3. The highway pavement structure utilizing waste residue according to claim 1 is characterized in that: The thickness of the lower layer is 20-24 cm.
4. The highway pavement structure utilizing waste residue according to claim 1 is characterized in that: The thickness of the base layer is 18-20 cm.
5. The highway pavement structure utilizing waste residue according to claim 1 is characterized in that: The thickness of the base layer is 18-20 cm.
6. The highway pavement structure utilizing waste residue according to claim 1 is characterized in that: The cement waste residue stabilized aeolian sand subbase comprises 5%-7% cement, 20%-50% power plant waste residue, and the remainder is aeolian sand.
7. The highway pavement structure utilizing waste residue according to claim 1 is characterized in that: The cement waste slag stabilized gravel aeolian sand base layer comprises 30%-40% gravel, 20-30% power plant waste slag, 6%-8% cement, and the balance is aeolian sand.
8. The highway pavement structure utilizing waste residue according to claim 7 is characterized in that: The particle size of the crushed stone is 10-30 mm.